Analisis Hubungan Kualitas Kehidupan Kerja Perawat dengan Kualitas Hidup Dimasa Pandemi Covid-19 di Rumah Sakit Umum Daerah M. Natsir - Febrian Rahmat Suwandi; Rahmi Fahmy; Dewi Murni; Nelwati Nelwati; Mira Susanti; Zifriyanti Minanda Putri (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
During the pandemic Covid-19, hospital must give the care more. It makes the medical staff condition changes, especially nurse. It makes the nurse got fatigue more, stressing of high-risk disease transmission, unwell work environment, lack of facilities and infrastructure and lack of communication among the medical staff. These condition influences the nursing work life quality such as: Work Life / Home Life, Work Design, Work Context, Work World. The aim of this research is to analyze the relationship between nursing work life quality and nursing life quality during Covid-19 pandemic at RSUD M. Natsir. The research design is quantitative descriptive by using cross sectional survey online. The population is all executive nurses who involve directly in Covid-19 patient care, namely 65 persons. The research instrument used questionnaire of quality of Nursing Work Life dan WHOQOL-BREFF. The data collection used frequency distributed analysis and SEM PLS 3.0. It’s gotten three dimension of nursing work life quality which is related with life quality significantly namely Work Design, Work Context and Work World with the value for each dimension 0,000, 0,025 and 0,019 means (significant value) < 0,05 while Work Life /Home Life dimension (significant value) s 0,497 > 0,05 with T statistic value 0,007 < T table 1,645 so this dimension does not have significant correlation with nursing work life. It is hoped the hospital management give more attention for work satisfaction, work burden, work communication, work image, salary, and safety during the duty in caring the patient of Covid-19.